POSTOPERATIVE CHANGES IN THE BEHAVIOR OF RATS AFTER ANESTHESIA WITH SEVOFLURANE - I. V. Belozertseva; O. A. Dravolina; V. O. Krivov; M. A. Tur; L. V. Mus; Yu. S. Polushin (Вестник анестезиологии и реаниматологии, 2018)
Goal: to assess behavior and cognitive functions of rats after certain aggressive impact imitating anesthesia with sevoflurane and surgery in the clinical practice. Methods. Male rats of Wistar stock (n = 20) were used to assess the long term behavioral effect of continuous (6 hours) of action of sevoflurane and abdomen surgery. For anesthesia induction 8 volumes of % sevoflurane in the air flow (2 l/min) were used, for anesthetic support it was 4 volumes of % and 1 l/min. During surgery the rat was placed on the heated operating table and the mask was used for anesthesia; laparotomy was performed; nestis was isolated and irritated for 10 seconds by massage done by the forefinger and thumb. After that the loop was placed into the abdomen and the wound was sutured layer by layer. Then in accordance with previously compiled protocol on simulation of postoperative cognitive disorders in the rats the following behavioral tests were performed in order to evaluate the degree of post-anesthetic depression – motion and exploratory activity, social behavior, novel object recognition, specific behavior and learning under acute stress and avoidance response, forced swimming, and sexual behavior. Spray rats (n = 8) were used as standard opponents for social behavior tests, and hormone-stimulated female rats (n = 15) were used for sexual behavior tests. Results. The results showed that long-term action of sevoflurane vapor and abdomen surgery caused behavioral changes in rats compared to animals from the control group in the number of tests: they are not able to recognize novel objects and slower repeat extrapolational deliverance response in 24 hours and 7 days after its conditioning. Sevoflurane made no significant impact on motion and exploratory activities in novel circumstances, duration of immobilization during forced swimming test, social and sexual behavior of male rats. Conclusions. Continuous action of sevoflurane and abdomen surgery causes cognitive deficiency in male rats, however the profile of changes is different from the one observed under the action of halothane.